Toilet talk an analysis of the latrinalias written in U.P. comfort rooms for women - Flores, Gene Marie L.; Salonga, Isabelle Victoria H. (College of Arts and Letters, University of the Philippines Diliman, 2009)
This study entitled "Toilet Talk : An Analysis of the Latrinalias Written in U.P. Comfort Rooms for Women" dealt with the language female latrinalia writers used to write on bathroom walls. This paper aimed to study and explain the nature of both graffiti and latrinalias. Furthermore, through the analysis of the language used, it endeavored to discoveer the issues faced by Filipino women at present. Data were gathered from alll comfort rooms available to students in the Palma Hall, Faculty Center, Math Building, and Main Library. A total of 225 units of latrinalias were recovered and categorized according to their themes using Wales and Brewer's Model. These were then analyzed using two frameworks, the Transitivity Model of Michael Halliday and the Critical Discourse Analysis (CDA)of Norman Fairclough. The categorization of data revealed that the most prevalent topics women wrote about were romantic and miscellaneous. It was also observed that new categories spawned and these include homosexual, sexual, advice, rant, academic, and even literary. In order to determine who affected whom in a sentence, the Transitivity Model was used. Participants and processes were labeled according to the types and from these, it was determined whether women were empowered by their acts of writing on bathroom walls. CDA was then utilized to interpret and contextualize the data. It was found out that the three most used processes in the data collected were the material, mental, and relational processes. The choices that women make in expressing themselves were influenced by the social context that the women are in. The act of writing graffiti was seen as women's attempt to veer away from the society's expectations of them as well as means of expressing themselves, albeit to a limited audience.